Iron accumulation and lipid peroxidation: implication of ferroptosis in hepatocellular carcinoma - Li, Xiaodong; Meng, Fanguang; Wang, Hankang; Sun, Liwei; Chang, Shulin; Li, Guijie; Chen, Feng (Frontiers in Endocrinology, 2024)
Ferroptosis is a type of controlled cell death caused by lipid peroxidation, which results in the rupture of the cell membrane. ferroptosis has been repeatedly demonstrated over the past ten years to be a significant factor in a number of diseases. The liver is a significant iron storage organ, thus ferroptosis will have great potential in the treatment of liver diseases. Ferroptosis is particularly prevalent in HCC. In the opening section of this article, we give a general summary of the pertinent molecular mechanisms, signaling pathways, and associated characteristics of ferroptosis. The primary regulating mechanisms during ferroptosis are then briefly discussed, and we conclude by summarizing the development of a number of novel therapeutic strategies used to treat HCC in recent years.Ferroptosis is a crucial strategy for the treatment of HCC and offers new perspectives on the treatment of liver cancer.